Estudo dos efeitos do laser de baixa intensidade na angiogênese em ruptura parcial do tendão calcâneo de ratos - Salate, Ana Claudia Bonome (Universidade Federal de São Carlos, 2004)
The purpose of this study was to analyze the 660 nm GaAlAs laser effect with 10 mW and 40 mW, during 10 seconds, on angiogenesis process and repair quality after partial lesion of Achilles tendon in rats. It was used 104 male rats, that 96 rats had been submitted to lesion by a falling of 186 g from a height of 20 cm, above the right tendon. These rats had been randomly divided in 3 groups, treated in 3 (n = 32), 5 (n = 32) and 7 (n = 32) days, respectively. Each of these groups was divided again into 4 subgroups, which were submitted to laser with mean output of 10 mW (n = 8) and 40 mW (n = 8), a sham treatment (n = 8), and a group with no treatment (n = 8). The analyzes were made by vessels count that have been previous prepared with nanquim ink and by a semiqualitative analyze of polynuclear cells presence, mononuclear cells presence, collagen organization and neovascularization. A fourth group with 8 animals was established as control, without lesion and used as reference for qualitative analyze. The comparison of the groups made evident that the animals submitted to laser showed more vessels number than the control groups (p<0,05) and the 40 mW subgroup showed better vascularization than the others after 3 days of irradiation. (p<0,01). The semiqualitative analyze showed statistical difference (p<0,05) when considering collagen organization and neovascularization in the comparison between the 10 mW, 40 mW and control. Qualitatively, the groups treated with laser showed better repair aspect. The results permit us to conclude that Low Level Laser Therapy with 660 nm promoted an increase of the blood vessels number and better repair quality and the mean output of 40 mW had begun the neovascularization precocious, showing significant difference after 3 days of application.
Study of the low level laser effect on angiogenesis in partial rupture of achilles tendon (tendo calcaneus) in rats
Keywords: Medicina experimental - rato; Laser de baixa potência; Tendão de Aquiles; Reparo tecidual; Low Level Laser; Achilles tendon; Neovascularization; Tendon repair; Irradiance; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL